Важливість користувацького досвіду в мобільному додатку - Єсіпова, К. Ю. (ХНУРЕ, 2021)
The difference between a good app and a bad one is often the quality of the user experience (UX). A good UX is what distinguishes successful programs from unsuccessful ones. Today, users expect a lot from the program: fast download time, easy to use and fun to interact. For an application to be successful, UX must be not just a secondary design aspect, but an important component.
Keywords: мобільний додаток; користувацький досвід